Clinical neuropsychology study guide and board review - Stucky, Kirk J.; Kirkwood, Michael W.; Donders, Jacobus (New York, NY : Oxford University Press, 2020)
"The Clinical Neuropsychology Study Guide and Board Review, second edition provides an easy to study volume with sample questions and recommended readings that are specifically designed to help individuals prepare for the ABCN written examination. In addition, this book can also be used as a teaching tool for graduate students and trainees at various levels. The book is divided into three sections: Section 1: Foundations of Clinical Neuropsychology; Section II: Fundamentals of Assessment; and Section III: Disorders and Conditions. The format is geared toward exam preparation and is much less dense than a typical textbook. Materials are provided in a concise, outlined manner, with liberal use of bullets, boxes, and illustrations/tables that allow readers to easily review and integrate information into their already established knowledge base. To augment the study guide, a recommended readings list at the end of each chapter provides references to more comprehensive materials considered important or seminal in each topic area"--
Includes bibliographical references and index.
Catalography
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Clinical neuropsychology -- Certification -- Study guides; Clinical neuropsychology -- Examinations, questions, etc; Clinical psychologists -- Certification -- Study guides; Study guides